Comparative analysis between physical activities and circulating lipids from pregnant individuals in Wuhan, from July 2024 to March 2025 - Xiaodan He; Yang Liu; Chaoli Chen; Bo Nie (Frontiers in Sports and Active Living)
BackgroundMaternal circulating lipid concentrations impact the risk of pregnancy complications and infant health outcomes. The associations between physical activity and circulating lipids during pregnancy remain inadequately understood.MethodsA study was conducted from July 2024 to March 2025, involving the recruitment of 520 pregnant women in Wuhan, China. The Pregnancy Physical Activity Questionnaire (PPAQ) scores were evaluated in trimesters. Circulating lipid profiles, including total triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), apolipoprotein A1 (APOA1) and apolipoprotein B (APOB) concentrations, were assessed at each trimester.ResultsThe daily energy expenditure of physical activity (EEPA) during the first, second, and third trimesters was recorded as 11.35, 9.07, and 9.48 metabolic equivalents-hour/day (METs-h/d). The EEPA in the first trimester was significantly greater than that in the second (p < 0.001) and third (p < 0.01) trimesters. Total daily EEPA levels were significantly elevated in individuals under 35 years old in the first trimester relative to both the second (p < 0.01) and third trimesters (p < 0.01), whereas no significant difference was found pregnant women over 35 years old. Compared to later trimesters, women in their first trimester exhibited significantly lower circulating levels of TG, TC, LDL, APOA1, and APOB (p < 0.0001), but not HDL. Interestingly, while TC, TG, LDL, APOA1, and APOB showed no significant differences across trimesters in older pregnancies, these markers underwent significant changes in younger women. Specifically, TG levels in the younger group increased progressively from the first to the second trimester, whereas no such trend was observed in the older population.ConclusionThis study suggests that increased physical activity during pregnancy is associated with lower lipid levels. Moreover, maternal age appears to have a significant impact on physical activity and the metabolism of circulating lipids during pregnancy.